The development and application of “PE + listed company” buyout model in China: a case study of Aier Eye Hospital Group - Li, Chenhao (2022)
This thesis studies the development and application of the “PE + Listed Company” Buyout model in China. It starts with a literature review on the relationship between private equity and listed companies, and on the “PE + Listed Company” Buyout model. It goes on to review the historic development of this model and offer an explanation for its uniqueness in Chinese market. In the next part, the study uses a framework inspired by previous researches and relevant concepts to study the application of this model through the case of Aier Eye Hospital. The framework analyzes the case through the motives of company’s acquisitions and use of the model, the process and integration approach, and the effects of the model. The study finds that Aier’s adoption of the model is motivated by the favorable industry trends and the characteristics of its own business model. Through the application of the “PE + Listed Company” Buyout model, Aier addresses its challenges to achieve growth while maintaining financial health.